Chest wall tuberculosis in children: a mimicker of bone tumour. Issue 4 (22nd April 2021) - Balasubramaniyan, Muthuvel; Verma, Sanjay; Dhawan, Sumeet Rajendra; saxena, Akshay Kumar
Abstract : Osteoarticular tuberculosis of flat bones of the chest wall such as sternum, scapula and rib is extremely rare in children. Because of its atypical clinical presentation mimicking malignant bone tumours, diagnosis remains a challenge. Histological and microbiological diagnosis remains confirmatory. Antitubercular therapy is the cornerstone in management.